Pragmatic Mobilization within Election Moment: Islamic Populism and Electoral Competition in Indonesia - Noor Rohman; Wiwik Setiyani; Holilah Holilah (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2022)
Most studies on the Islamic populism in Indonesia have only focussed on identity politics or political economy aspects. However, little attention has been paid to examining Islamic populism as an electoral campaign strategy in much detail. Therefore, this article would like to discusses how and to what extent Islamic populism works in the 2019 presidential election. We argue that Islamic populism is a pragmatic mobilization for winning electoral contestation which renews its legitimacy in election moments to gain political support. The argument builds based on the case study of Gerakan Nasional Pembela Fatwa Ulama in the 2019 presidential election. Utilizing qualitative method strategy, our findings in this study indicate that the logic of electoral political winning seems dominant in the mobilization of Islamic populism. At the moment of the campaign, this mobilization used religious sentiments to get voter support. Such religious-based mobilization only invites the sympathy of exclusive supporter segments and difficult to build alliances with broader elements of society because of it tends to be pragmatic. At the same time, this pragmatism also eroded the political legitimacy that it was trying to recreate and maintain during the election moment by holding Ijtima’ Ulama forum.